Clinical characteristics and risk factors analysis of allergic bronchopulmonary aspergillosis combined with bronchiectasis - He, Qian; Li, Min; Cao, Jiaqi; Zhang, Ming; Feng, Chunlai (Frontiers in Medicine, 2025)
BackgroundAllergic bronchopulmonary aspergillosis (ABPA) is a complex pulmonary disorder caused by a hypersensitivity reaction to Aspergillus colonizing the airways. Research on the clinical characteristics and risk factors of ABPA in patients with bronchiectasis is limited. This study aimed to investigate the clinical features and risk factors of ABPA in patients with bronchiectasis to improve clinical recognition.MethodsWe retrospectively collected clinical data from bronchiectasis patients hospitalized at the Third Affiliated Hospital of Soochow University between September 2017 and December 2021.ResultsA total of 251 patients were included in the analysis, of which 46 were confirmed to have ABPA with bronchiectasis. The remaining 205 patients served as control group. There were no significant differences in clinical symptoms (fever, cough, hemoptysis, chest pain, wheezing) between the two groups. However, blood eosinophil count and total IgE levels were significantly higher in the ABPA group compared to the control group. Both univariate and multivariable analyses revealed that a higher bronchiectasis severity index (BIS), frequent pet contact, hypoproteinemia, and Aspergillus colonization significantly increased the risk of developing ABPA in bronchiectasis.ConclusionThe clinical symptoms of ABPA in patients with bronchiectasis are clinically indistinguishable from those of non-ABPA bronchiectasis A higher BIS, frequent pet contact, hypoproteinemia, and Aspergillus colonization are identified as key risk factors for ABPA development in bronchiectasis.